Preparation and thermal properties of the graphene–polyolefin adhesive composites: Application in thermal interface materials. Issue 12 (December 2015) - Cui, Tengfei; Li, Qiang; Xuan, Yimin; Zhang, Ping
Abstract: Graphene mixed with epoxy for thermal interface material (TIM) has been well researched. However, some issues emerge when epoxy is used as matrix material, such as overflow problem, non-uniform thickness, needing solidification time, etc. In order to avoid the above issues, a new high performance phase change material (PCM) is prepared by incorporating graphene with polyolefin hot melt pressure sensitive adhesive (HMPSA). The thermal conductivity and hardness of graphene/HMPSA (GHMPSA) composites are both measured and found to be increased with the increase of filled graphene. Due to the increasing hardness, the smallest thermal contact resistance is achieved with 6 wt.% graphene, not 10 wt.%, even the biggest thermal conductivity of GHMPSA is 5.6 W/(mK) with 10 wt.% graphene. The comparison between the present GHMPSA TIM and other commercial TIMs indicates that the present GHMPSA composite is a commendable TIM in reducing thermal contact resistance. Highlights: A new high-performance TIM based on graphene and polyolefin is prepared. The relations between the properties and component fractions of the present TIM are studied. Thermal contact resistance of the present TIM is measured and analyzed.